Electron spin resonance studies on single crystalline Fe3O4 films - (:unkn) unknown (ELSEVIER SCIENCE BV, 2003)
The effects of surface coating (Co and/or CoxOy) on magnetic anisotropies in single crystalline Fe3O4 films with different thickness that were epitaxially grown on MgO (100) substrate have been studied by electron spin resonance (ESR) technique. The angular dependent ESR spectra were analysed by using well-known SWR theory and the magnetic anisotropy parameters were deduced. The magnetic anisotropies are deeply affected from both film thickness and surface coating conditions. Magneto-crystalline cubic anisotropy (30 and 60 Oe for 110 and 2771 Angstrom thick films, respectively) is much smaller compared to its value for the bulk sample of the same compound (H-k = 2K(1) /M = 460 Oe). The effective magnetization is influenced by the surface coating as well. The spectra for surface-coated films broaden especially for Co3O4-coated samples. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: ESR; magnetic anisotropy; magneto-crystalline energy; MGO(100); BEHAVIOR; SURFACE